Upaya Meningkatkan Hasil Belajar Matematika dengan Menerapkan Model Pembelajaran Round Club berbantuan Media Monopoly Game Smart pada Peserta Didik Kelas V-B Di SDN-1 Sabaru Palangka Raya Tahun Pelajaran 2016/2017: Efforts to Improve Learning Outcomes of Mathematics by Implementing Round Club Learning Models Assisted by Smart Monopoly Game Media in Class V-B Students at SDN-1 Sabaru Palangka Raya 2016/2017 Academic Year - Rani Nidya Wati; Arif Supriyadi (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2017)
This study aims to: (1) Describe the activities of learning Mathematics of VB graders at SDN-1 Sabaru Palangka Raya in the 2016/2017 Academic Year on the implementation of the Round club model assisted by Monopoly Game Smart media, (2) Improving the learning outcomes of Mathematics in VB class students in SDN-1 Sabaru Palangka Raya Academic Year 2016/2017 after the implementation of the Round club model assisted by Smart Game Monopoly media. The type of research used by researchers is Class Action Research (CAR) with research subjects of all VB class students at Sabaru Palangka Raya SDN-1, totaling 22 students. Data collection techniques in this study use observation and tests. Data analysis uses qualitative data analysts. And quantitative. The results of this study indicate that: (1) Activity of VB class students at SDN-1 Sabaru Palangka Raya in the 2016/2017 school year in Mathematics learning after applying the Round Club learning model assisted by Monopoly media Smart Games are better, because students are active, enthusiastic , listen to the teacher's explanation and be enthusiastic in following the learning process. The results of the teacher observation on teaching and learning activities were carried out by observer I and observer II during the Mathematics learning process in the first cycle. The common aspect of teacher activity was 3.61 in the excellent category, and the universal element of students was 3.40 in the very type. Well. (2) There is an increase in Mathematics learning outcomes by applying the Round Club learning model assisted by Monopoly Game Smart media on V-B grade math subjects at SDN-1 Sabaru Palangka Raya in the academic year 2016/2017. This is indicated by the learning outcomes seen through the class average in the first cycle which is equal to 78.63, and the completeness percentage of students in classical is 100%, from the predetermined provisions, namely for KKM of 65 and completeness criteria in traditional 85%.